Removal selectivity of Prometheus: A new extracorporeal liver support device - Rifai, Kinan (Baishideng Publishing Group Co., Limited, 2006)
AIM: To evaluate whether treatment with the Prometheus(®) system significantly affects cytokines, coagulation factors and other plasma proteins. METHODS: We studied nine patients with acute-on-chronic liver failure and accompanying renal failure. Prometheus(®) therapy was performed on 2 consecutive days for up to 6 h in all patients. Several biochemical parameters and blood counts were assessed at regular time points during Prometheus(®) treatment. RESULTS: We observed a significant decrease of both protein-bound (e.g. bile acids) and water-soluble (e.g. ammonia) substances after Prometheus(®) therapy. Even though leukocytes increased during treatment (P < 0.01), we found no significant changes of C-reactive protein, interleukin-6, and tumor necrosis factor-α plasma levels (all P  > 0.5). Further, antithrombin 3, factor II and factor V plasma levels did not decrease during Prometheus(®) therapy (all P  > 0.5), and the INR remained unchanged (P  = 0.4). Plasma levels of total protein, albumin, and fibrinogen were also not altered during Prometheus(®) treatment (all P  > 0.5). Finally, platelet count did not change significantly during therapy (P = 0.6). CONCLUSION: Despite significant removal of protein-bound and water-soluble substances, Prometheus(®) therapy did not affect the level of cytokines, coagulation factors or other plasma proteins. Thus, the filters and adsorbers used in the system are highly effective and specific for water-soluble substances and toxins bound to the albumin fraction.